The Efficacy of Project-Based Learning in Fostering Linguistic and Motor Development in Early Childhood - Simorangkir, Melda; Deliviana , Evi (JURNAL PENDIDIKAN USIA DINI, 2026)
The aim of this study is to determine the effectiveness of project-based learning (PjBL) in enhancing the linguistic and motor intelligence of early childhood students. A mixed-method approach was employed, combining quantitative data from child development rubrics with qualitative data from observations, interviews, and activity documentation. An experimental design was used, with a control group following conventional learning methods and an experimental group receiving project-based learning. The findings indicate that PjBL techniques significantly improve linguistic and motor intelligence. Specifically, the average linguistic intelligence score of the experimental group increased from 62.4 (pre-test) to 83.7 (post-test), while motor intelligence scores rose from 58.9 to 80.1. Through creative activities such as making picture stories and engaging in collaborative play, children in the experimental group demonstrated enhanced speaking, writing, and both fine and gross motor skills. Qualitative analysis also revealed increased confidence, teamwork, and emotional engagement among the children. Key success factors included teacher training, parental involvement, and a supportive learning environment. These findings have practical implications for educators, policymakers, and parents: integrating PjBL into early childhood curricula can foster holistic child development, improve school readiness, and bridge the gap between academic and socio-emotional growth. Supporting this approach through policy, curriculum planning, and parental outreach is essential for sustainable implementation